Culture conditions influence satellite cell activation and survival of single myofibers - Alessandra Renzini; Anna Benedetti; Marina Bouché; Leopoldo Silvestroni; Sergio Adamo; Viviana Moresi (European Journal of Translational Myology, 2018)
Single myofiber isolation protocols allow to obtain an in vitro system in which the physical association between the myofiber and its stem cells, the satellite cells, is adequately preserved. This technique is an indispensable tool by which the muscle regeneration process can be recapitulated and studied in each specific phase, from satellite cell activation to proliferation, from differentiation to fusion. This study aims to clarify the effect of different culture conditions on single myofibers, their associated satellite cells, and the physiological behavior of the satellite cells upon long term culture. By direct observations of the cultures, we compared different experimental conditions and their effect on both satellite cell behavior and myofiber viability.